Natural bauxite nanosheets: A multifunctional and sustainable 2D nano-reinforcement for high performance polymer nanocomposites. (10th November 2019) - Zabihi, Omid; Ahmadi, Mojtaba; Ghandehari Ferdowsi, Mahmoud Reza; Li, Quanxiang; Fakhrhoseini, Seyed Mousa; Mahmoodi, Roya; Ellis, Amanda V.; Naebe, Minoo
Abstract: Synthesis of two dimensional (2D) nanomaterials from natural resources for the fabrication of high performance multifunctional polymer nanocomposites has gained great interest. Herein, we report on a facile method for synthesizing 2D bauxite nanosheets (BNS) directly from its ore using a combination of ball-milling and hydrothermal processes. Successful preparation of the BNS was confirmed using scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET) specific surface area, and particle size distribution. The changes in phases monitored by X-ray diffraction (XRD), before and after ball-milling and hydrothermal treatment, indicated the presence of γ-Al2 O3 in the BNS structure. As a promising application, the BNS was introduced into a thermosetting epoxy resin. Thermal analysis and rheological analyses were performed to understand the influence of BNS on the curing and processing of the epoxy matrix. Higher mechanical performance of the epoxy resin reinforced with BNS was achieved and characterized using tensile, flexural, and dynamic thermo-mechanical (DMT) analyses. Thermal stability of the epoxy nanocomposites containing BNS were also evaluated using thermogravimetry analyses (TGA). The overall results indicate that BNS can effectively serve as a cost-effective multifunctional reinforcing agent in fabrication of high performance epoxy nanocomposites.